PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi pada konsumen Rumah Makan Inggil di Kota Malang) - Cundhamani Caraka Gana (Manajemen Bisnis, 2017)
The purpose of this study was to determine the effect of store atmosphere consisting of instore atmosphere and outstore atmosphere on purchasing decisions and to find out the store atmosphere that consists of instore atmosphere and atmosphere outstore the dominant influence on the purchase decision. This type of research is (descriptive reasearch) with a quantitative approach, using primary data taken from questionnaire respondents, namely consumer Inggil Restaurant in Malang. The sampling technique using a non-probability sampling with a sample size of 100 respondents. Data were analyzed using multiple linear regression analysis.Based on the results of research and discussion that has been done it can be concluded that 1) there are significant atmosphere and outstore atmosphere instore partially and simultaneously on purchasing decisions and 2) instore atmosphere as dominant influence on purchase decisions Inggil Restaurant in Malang.